Carlos Alberto Seguin. (1907 - 1995 ) Semblance - Cabrejos Pinto, José (1995)
On Saturday August 26 last, ended the existence of the Master Dr. Carlos Alberto Seguin Escobedo. His departure leaves a major gap in the national psychiatry since his death cycle of the great masters of Psychiatry Peruvian closes.